Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1200/jco.2007.13.2720
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Erlotinib or Standard Chemotherapy in Patients With Advanced Non–Small-Cell Lung Cancer and a Performance Status of 2

Abstract: Unselected patients with advanced NSCLC and PS 2 are best treated with combination chemotherapy as first-line therapy. Erlotinib may be considered in patients selected by clinical or molecular markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
122
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(128 citation statements)
references
References 9 publications
(2 reference statements)
5
122
0
1
Order By: Relevance
“…Billingham and Cullen found superior palliation among PS 2 patients in comparison to PS 0/1 [12] in two randomized trials using mitomycin, ifosfamide and cisplatin in the treatment of unresectable NSCLC [25]. Furthermore, in a recent randomized phase II study on first line erlotinib versus standard chemotherapy of PS 2 advanced NSCLC patients, HRQOL tended to improve rather than worsen in both treatment arms [26]. In fact, the authors concluded that unselected advanced NSCLC PS 2 patients are best treated with combination chemotherapy in first-line.…”
Section: Discussionmentioning
confidence: 99%
“…Billingham and Cullen found superior palliation among PS 2 patients in comparison to PS 0/1 [12] in two randomized trials using mitomycin, ifosfamide and cisplatin in the treatment of unresectable NSCLC [25]. Furthermore, in a recent randomized phase II study on first line erlotinib versus standard chemotherapy of PS 2 advanced NSCLC patients, HRQOL tended to improve rather than worsen in both treatment arms [26]. In fact, the authors concluded that unselected advanced NSCLC PS 2 patients are best treated with combination chemotherapy in first-line.…”
Section: Discussionmentioning
confidence: 99%
“…In one trial, pfs was longer in the egfr inhibitor group: 4.57 months for erlotinib versus 2.53 months for vinorelbine (hr: 0.6444; 95% ci: 0.4325 to 0.9601; p = 0.0308) 21 . In five trials, pfs was longer in the chemotherapy group 13,15,17,19,20 . Several of the trials found that pfs significantly favoured chemotherapy 13,15,19 .…”
Section: First-line Treatmentmentioning
confidence: 99%
“…In five trials, pfs was longer in the chemotherapy group 13,15,17,19,20 . Several of the trials found that pfs significantly favoured chemotherapy 13,15,19 . One trial examined time to progression and found that it was longer with chemotherapy, but not significantly so 20 .…”
Section: First-line Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed a lower PFS and OS compared with chemotherapy. 179 A randomized trial comparing gefitinib versus placebo in patients not candidates for chemotherapy with PS 2-3 revealed no advantage in OS and PFS for patients receiving gefitinib. Only in the subgroup with FISH-positive EGFR was there a statistically significant advantage in PFS.…”
Section: Systemic Treatment In Poor Performance Status Patientsmentioning
confidence: 99%